PEMBERDAYAAN UMKM MELALUI DIGITALISASI PELAPORAN KEUANGAN DALAM UPAYA PERLUASAN AKSES PEMBIAYAAN - Nurhayati, Enung; Rahmawati, Teti; Wiharno, Herma (Nindikayla Institute, 2023)
The Covid 19 pandemic that occurred in all countries in the world has had an extraordinary impact on people's lives, including the continuity of micro, small, and medium enterprises (MSMEs). During the pandemic, there was a change in people's consumption patterns of goods and services from offline to online. This encourages MSMEs to sell online so that they can survive and continue to grow. The survival ability of MSMEs that sell online is stronger than MSMEs that only sell offline. The use of digitalization is also carried out in financial reporting. Based on the results of a survey of MSME actors in Babatan village, Kadugede District, Kuningan Regency, there are still many MSMEs that have not taken advantage of digitalization in the preparation of financial statements. This encourages the author to carry out training and assistance in digitizing MSME financial reporting using an android mobile application. The benefits obtained are that MSME actors can prepare financial reports more easily and quickly so that they can expand access to financing through banking